KUALITAS ORGANOLEPTIK DAGING SE’I YANG DIOLAH DARI DAGING SAPI BALI BETINA AFKIR (Organoleptic quality of se’i made from bali cull cow beef) - Kiki R. Adjam; Gemini E.M. Malelak; Bastari Sabtu (Universitas Nusa Cendana, 2020)
Aim of this study was to evaluate quality of se’i (Rotennese smoke meat) made from cull Bali cow meat. Completely randomized design 3x3 was used in this study. Meat taken from cull Bali cow with body condition skore (BCS) 2 (thin), 3 (moderate) and 4 (slightly fat). Each BCS had three replicates. Parameters observed included taste, color, aroma, pH value and fat oxidation. The results showed that BCS had a highly significant effect (P <0.01) on color and taste, had a significant effect (P <0.05) on fat oxidation, had no significant effect (P> 0.05) on aroma and pH. Se,i made from BCS 4 had a slightly dark red color, the best taste and the highest fat oxidation rate, whereas se'i prepared from BCS 3 has a slightly dark red color, medium taste and lowest fat oxidation rate. It is concluded that the best quality of se’i produced in this study was made from BCS 4,however, it was necessary to add antioxidants to retard fat oxidation rate. Whereas if used BCS 3 it is better to add some additives to improve the taste.